2020
DOI: 10.5851/kosfa.2020.e15
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Lactobacillus brevis KU200019 and Synergistic Activity with Fructooligosaccharides in Antagonistic Activity against Foodborne Pathogens

Abstract: This study aims to evaluate the probiotic properties of Lactobacillus brevis (L. brevis) KU200019 and the synergistic activity with prebiotics on antimicrobial activity, and the potential application as an adjunct culture in fermented dairy products. The commercial strain, L. brevis ATCC 14869 was used as reference strain. L. brevis KU200019 was showed higher viability in simulated gastric (99.38±0.21%) and bile (115.10±0.13%) conditions compared to reference strain. L. brevis KU200019 exhibited antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…This bacteria can be applied to use in industrial and food technology and normally defined as GRAS (Generally Recognized As Safe) 32 . Some strain of L. brevis presented probiotic properties, e.g., antioxidant properties 33 , anti-caries activity 34 , immunomodulating activity 35 and synergistic with prebiotic for antimicrobial activity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This bacteria can be applied to use in industrial and food technology and normally defined as GRAS (Generally Recognized As Safe) 32 . Some strain of L. brevis presented probiotic properties, e.g., antioxidant properties 33 , anti-caries activity 34 , immunomodulating activity 35 and synergistic with prebiotic for antimicrobial activity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been defined as live microbes that confer health benefits on the host when administered in appropriately amounts (FAO/WHO, 2006; Lee et al, 2019). Probiotics can balance the intestinal microflora, which are involved in the epithelial barrier of intestines, competition with disease-causing agents, attachment to the epithelial wall of intestines, production of anti-pathogen elements, and enhancement of the immune system of the host (Abdulamir and Hafidh, 2020;Jang et al, 2019;Kariyasawasam et al, 2020). Bifidobacterium bifidum and Streptococcus thermophilus showed a decline in diarrheal incidents and reduction of rotavirus titers in a meta-analysis (Szajewska et al, 2019).…”
Section: Prophylactic Therapy By Probioticsmentioning
confidence: 99%
“…ns : There were no significant differences between columns (p < 0.05) in Duncan's multiple range tests after one-way ANOVA. 3 FER: Food efficiency ratio = (weight (g)/food intake (g)) × 100.…”
Section: Body Weight Food Intake and Feed Efficiency Ratio (Fer)mentioning
confidence: 99%
“…Recently, many people have become increasingly interested in functional foods that contain natural ingredients to maintain their health or prevent diseases [1,2] and many food scientists have eagerly studied bio-functional materials such as probiotics, phytochemicals, organic materials produced by microorganisms (fermentation or bioconversion). In particular, lactic acid bacteria (LAB) are considered the most commonly used biomaterials, as studies have shown that the LAB-mediated treatment has many benefits in illnesses, such as foodborne diseases, inflammation, intestinal diseases, and cancer [3][4][5][6]. Many kinds of LAB can be isolated from kimchi, which is a representative traditional Korean food manufactured by naturally fermenting the vegetables such as cabbage and radish at a low temperature.…”
Section: Introductionmentioning
confidence: 99%